No branch left behind: tracking terrestrial biodiversity from a phylogenetic completeness perspective - Pinto Ledezma, Jesús N. (2023)
Biodiversity is ultimately the outcome of millions of years of evolution; however, due to increasing human domination of the Earth, biodiversity in its multiple dimensions is changing rapidly. Here, we present “phylogenetic completeness” (PC) as a concept and method for safeguarding Earth's evolutionary heritage by maintaining all branches of the tree of life. Using data for five major terrestrial clades, we performed a global evaluation of the PC approach and compared the results to an approach in which species are conserved or lost at random. We demonstrate that under PC, for a given number of species extinctions, it is possible to maximize the protection of evolutionary innovations in every clade. The PC approach is flexible, may be used to conduct a phylogenetic audit of biodiversity under different conservation scenarios, complements existing conservation efforts, and is linked to the post-2020 UN Convention on Biodiversity targets.